2020
DOI: 10.1038/s41467-020-15180-5
|View full text |Cite
|
Sign up to set email alerts
|

SSRP1-mediated histone H1 eviction promotes replication origin assembly and accelerated development

Abstract: In several metazoans, the number of active replication origins in embryonic nuclei is higher than in somatic ones, ensuring rapid genome duplication during synchronous embryonic cell divisions. High replication origin density can be restored by somatic nuclear reprogramming. However, mechanisms underlying high replication origin density formation coupled to rapid cell cycles are poorly understood. Here, using Xenopus laevis, we show that SSRP1 stimulates replication origin assembly on somatic chromatin by prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…[12] Overall these changes might be promoted by increased nucleosome mobility along the DNA induced by the loss of histone H1 and might be independent of direct effects of SSRP1 and the FACT complex on core histone association to DNA as no changes were found in histone H2A, H2B, H3, and H4 binding to chromatin by overexpressing SSRP1 in Xenopus. [12] Significantly, the N-terminus domain of SSRP1 was shown to bind H1 with high affinity and, surprisingly, was demonstrated to be necessary and sufficient to mediate SSRP1 effects, which were independent of SPT16 subunit. Recent work has suggested that SSRP1 can form homodimers in vitro that bind H3-H4 histones through the same PH2 domain involved in the formation of heterodimers with SPT16.…”
Section: The Fact Complex Controls Replication Origin Selectionmentioning
confidence: 93%
See 4 more Smart Citations
“…[12] Overall these changes might be promoted by increased nucleosome mobility along the DNA induced by the loss of histone H1 and might be independent of direct effects of SSRP1 and the FACT complex on core histone association to DNA as no changes were found in histone H2A, H2B, H3, and H4 binding to chromatin by overexpressing SSRP1 in Xenopus. [12] Significantly, the N-terminus domain of SSRP1 was shown to bind H1 with high affinity and, surprisingly, was demonstrated to be necessary and sufficient to mediate SSRP1 effects, which were independent of SPT16 subunit. Recent work has suggested that SSRP1 can form homodimers in vitro that bind H3-H4 histones through the same PH2 domain involved in the formation of heterodimers with SPT16.…”
Section: The Fact Complex Controls Replication Origin Selectionmentioning
confidence: 93%
“…Consistent with this, histone H1 binding to sperm chromatin directly inhibits ORC and MCM chromatin loading. [12] The mechanism by which histone H1 directly prevents ORC binding remains to be established and could be related to histone H1-mediated inhibition of chromatin remodeling, [70] competition with other chromatin-binding proteins [71] or nucleosomes stabilization. [71,72] Importantly, these inhibitory actions of H1 can be reversed, as demonstrated by recent experiments involving SSRP1, which together with SPT16 forms the chromatin remodeling FACT complex.…”
Section: Histone H1 Regulates Chromatin Structure and Functionmentioning
confidence: 99%
See 3 more Smart Citations